(untitled) (Journal of Economic Research & Business Administration, 2022)
Economic internationalization in this century is an irreversible process, and the driving forces of this process are transnational structures, business organizations, globalization of financial markets, political and regulatory conditions for business scaling. An integral element of the world economy is international accounting, harmonization and standardization of its principles, developed on its basis, considered in many aspects and at many levels. The article examines the process of harmonization of the accounting system in Poland with the International Financial Reporting Standards (IFRS). The stages of development of the convergence of Polish GAAP with IFRS in a historical perspective are shown, with particular attention to the harmonization of accounting in the European Union, as the main trigger for the implementation of IFRS in Poland. Some distinguishing features of GAAP from IFRS are analyzed and conclusions are drawn. The purpose of the study is to show the stages of harmonization of Polish GAAP with IFRS and highlight some of the distinguishing characteristics between Polish GAAP and IFRS. To achieve this goal, the following tasks are set: - a review of the literature of Polish researchers on the harmonization of accounting and the development of accounting in Poland over the past 20-40 years. - to consider the harmonization of the European Union as the main trigger affecting the Polish accounting system - highlight the development of Polish GAAP after accession to the European Union and explore the stages of harmonization of Polish GAAP with IFRS. - show some distinctive characteristics of Polish GAAP and IFRS and draw conclusions. When writing this work, qualitative research methods were used, such as observation, the scientific method, case study, expert interviews and content analysis. Key words: economic internationalization, IFRS, harmonization, standardization, GAAP.